IoT feasibility aspects of mold temperature monitoring and casting simulation for smart foundry. (2020) - Barot, R.S.; Patel, H.; Devmurari, R.; Shah, K.; Sharma, B.; Shah, Jay
Abstract: The world is moving in the direction of digitalization demanding change to smart manufacturing. Utilization of smart manufacturing with adoption of Internet of Things (IoT) in the foundry industry gives benefits and help to overcome challenges. In cast iron foundry rejection due to solidification defect like sand drop, crack, pinholes, shrinkage cavity, cold shut, misrun which can be reduced with help of directional solidification. For solidification analysis cooling curve monitoring needs time and effort. For analysis the correct method of data collection and monitor is required. In present work authors have made an attempt to use solution that is anticipated is Autocast_X1 software simulation and development of low cost IoT solution for smart foundry. In Autocast-X1 software simulation is performed and defect analysis is carried out. It is the effective way to improve design and helps to reduce trial runs and efforts. Thermocouple directly placed in a mould cavity to monitor temperature. It is helpful to study cooling curves and quality check of solidification defects. Experimental investigations are carried out to map simulation result of mold temperature with real time data with help of thermocouples placed at mold interface. Mold-metal interface data using controllers and amplifier are stored in mobile for live monitoring. Use low cost IoT platform reduces supervisor movement and saves time by providing casting solidification data at his work place. With the help of casting simulation early check of effective gating system and defect prediction enables reasonable productivity and quality. IoT solution helps to monitor foundry practices, reduction in human effort, paperwork, and reduction in cost with rise of profit margin.